P23 Predictors of mortality in progressive fibrosing interstitial lung disease patients treated with Nintedanib: real-world data from a single ILD specialist centre. (11th November 2022) - Stranks, L; Newman, K; Garfoot, T; Morris, H; Zakis, K; Swale, J; Greaves, M; Stanel, S; Ramjug, S; Avram, C; Blaikley, J; Leonard, C; et al.
Abstract : Introduction/Objectives: Nintedanib is a tyrosine kinase inhibitor demonstrated to slow the rate of progression of fibrotic interstitial lung diseases (ILD). Originally available solely for the treatment of idiopathic pulmonary fibrosis (IPF), access to Nintedanib became available in the UK for those with non-IPF progressive fibrosing ILD (PFILD) in October 2019, on a Named Individual Patient Supply (NIPS) from Boehringer UK. Longitudinal data from this cohort has been limited thus far and predictors of mortality remain unclear. This study aims to identify factors influencing mortality in the PFILD cohort treated with Nintedanib. Methods: 47 PFILD patients receiving Nintedanib on a NIPS were identified from our ILD specialist centre database from November 2019 to January 2021 (treatment start date). All patients had been discussed in our ILD multidisciplinary meeting and met criteria for PFILD according to the INBUILD trial (Flaherty KR, et al. Nintedanib in Progressive Fibrosing Interstitial Lung Diseases. N Engl J Med. 2019 Oct 31:381(18):1718–1727). Demographic, clinical, lung function, and radiological parameters were collected from the hospital's electronic patient record system. The primary outcome was survival. Results: Of the 47 PFILD patients receiving Nintedanib, 22 (47%) were still alive in June 2022 ( table 1 ). Baseline mean forced vital capacity (FVC) and diffusing capacity for carbon monoxide (DLCO) were higher in this cohort (57.6% predicted and 38.9% predicted, respectively), compared to those who were deceased (48.2% predicted and 28.2% predicted, respectively). Those who were deceased had a higher mean dose of oral Prednisolone (15 mg daily), compared to those who were still alive (10.8 mg daily). There was no significant difference associated with Prednisolone use overall. Longer median duration of Nintedanib administration was also associated with a statistically significant difference in mortality (20 months compared to 7 months, p<0.01). There was no statistically significant difference when considering age at commencement, sex, PFILD subtype or diagnostic criteria, smoking status, comorbidities, oxygen therapy, use of concomitant immunosuppression, acute ILD exacerbations, or radiological pattern. Conclusions: In this PFILD cohort, lower baseline FVC and DLCO, higher dose of prednisolone, and shorter duration of treatment with Nintedanib were associated with increased mortality.